E-COMMERCE STRATEGY INTERCONTINENTAL BALI RESORT - I Gusti Putu Ngurah Budiasa; I Wayan Yudi Suriyasa (ASEAN Journal on Hospitality and Tourism, 2015)
Global and dynamic competition is one of the challenges for hospitality industry. Internet is a global network of interconnected networks. In 2012, the approximately 2.4 billion users connected to the internet worldwide represent just 34,3% of the global population. In these conditions, the usage of internet technology in business strategy plays an important role to assure service quality optimization, provide ultimate customer value and/or increase company profitability. E-commerce is the subset of e-business focused on transaction. The average contribution of e-commerce business in InterContinental Bali Resort (ICBR) showed 18.39% in the last five years. However, data 2012 showed negative performance whereby from19.17% in 2011 down to 17.72% or decrease 1.45% or 2.586 room nights, below average market performance area which range between 20 "“ 25%. This study wants to analyze and discuss the e-commerce strategies of ICBR. The research concluded some strategies, such as; managing hotel website, maintaining reservation access and security transactions of credit cards were runned very well. Other strategies need to be further improved and developed, such as; offering the best availability rates and customer loyalty program. In contrast, the speed of customer response and attractive promotion packages need much improved.